Bioethics and truthfulness: When the doctor’s word can deepen the patient’s helplessness - Rilova Salazar, Felipe Arturo (Acta Bioethica, 2020)
The reflections recorded in this article consider the way in which the general practitioner can interpret and apply the rule referring to the patient’s right to know the truth based on their assimilation and understanding schemes, closely related to the philosophy implicit in the theoretical model of contemporary medicine. The need is considered that the rule that prescribes the “right of the patient to know the truth” be adapted to the degree of helplessness of each case, in order not to make this right an obligation that contradicts the bioethical principle of responsibility that it indicates the personalistic bioethical current. Reference is made to “doctor’s phobia” -iatrophobia- as an expression of specific psychic damage resulting from inappropriate application of “truthfulness.” In order to a practice that has ceased to be “assistance” (derived from the Latin “assistere”: to be next to) to become strictly therapeutic, reference is made to the challenge of coping outside the iron positivist matrices in which the medical model is installed, pointing out the obstacles that the Bioethics Committees must surely overcome when it comes to urging responsible compliance with the truth rule.